Comparative Assessment of the Apoptotic Potential of Silver Nanoparticles Synthesized by Bacillus Tequilensis and Calocybe Indica in MDA-MB-231 Human Breast Cancer Cells: Targeting p53 for Anticancer Therapy [Corrigendum] - Gurunathan S; Park JH; Han JW; Kim J (International Journal of Nanomedicine, 2022)
Gurunathan S, Park JH, Han JW, Kim J. Int J Nanomedicine. 2015;10(1):4203–4223. It was bought to the authors attention that there are errors in Figure 14 on page 4218. The DAPI images, panels B-AgNPs + PFT-α and F-AgNPs + PFT-α were duplicated. The error was introduced during the article revision process and went unnoticed. The authors wish to apologize for this oversight and for any inconveniences caused. The correct Figure 14 is as follows.